Type 2 Innate Lymphoid Cells Accumulate in the Brain After Hypoxia-Ischemia but Do Not Contribute to the Development of Preterm Brain Injury - Zelco, Aura; Rocha-Ferreira, Eridan; Nazmi, Arshed; Ardalan, Maryam; Chumak, Tetyana; Nilsson, Gisela; Hagberg, Henrik; Mallard, Carina; Wang, Xiaoyang (Frontiers in Cellular Neuroscience, 2020)
Background: The immune system of human and mouse neonates is relatively immature. However, innate lymphoid cells (ILCs), commonly divided into the subsets ILC1, ILC2, and ILC3, are already present in the placenta and other fetal compartments and exhibit higher activity than what is seen in adulthood. Recent reports have suggested the potential role of ILCs, especially ILC2s, in spontaneous preterm labor, which is associated with brain damage and subsequent long-term neurodevelopmental deficits. Therefore, we hypothesized that ILCs, and especially ILC2s, play a role in preterm brain injury. Methods: C57Bl/6J mice at postnatal day 6 were subjected to hypoxia-ischemia (HI) insult induced by left carotid artery ligation and subsequent exposure to 10% oxygen in nitrogen. The presence of ILCs and ILC2s in the brain was examined at different time points after HI. The contribution of ILC2s to HI-induced preterm brain damage was explored using a conditionally targeted ILC2-deficient mouse strain (Rorαfl/flIL7rCre), and gray and white-matter injury were evaluated at 7 d post-HI. The inflammatory response in the injured brain was assessed using immunoassays and immunochemistry staining. Results: Significant increases in ILCs and ILC2s were observed at 24 h, 3 d, and 7 d post-HI in the injured brain hemisphere compared with the uninjured hemisphere in wild-type mice. ILC2s in the brain were predominantly located in the meninges of the injured ipsilateral hemispheres after HI but not in the brain parenchyma. Overall, we did not observe changes in cytokine/chemokine levels in the brains of Rorαfl/flIL7rCre mice compared with wild type animals apart from IL-13. Gray and white-matter tissue loss in the brain was not affected after HI in Rorαfl/flIL7rCre mice. Correspondingly, we did not find any differences in reactive microglia and astrocyte numbers in the brain in Rorαfl/flIL7rCre mice compared with wild-type mice following HI insult. Conclusions: After HI, ILCs and ILC2s accumulate in the injured brain hemisphere. However, ILC2s do not contribute to the development of brain damage in this mouse model of preterm brain injury.